Causal Relationship Between the BRICS Countries’ Stock Performances During COVID-19: Array - Ngwakwe, Collins (Acta Universitatis Danubius. Œconomica, 2020)
Stock market performance relationships during disease epidemics is nebulous. Objective. The objective of this paper is to analyse the causal relationship between the BRICS countries’ stock market performance during the COVID-19 period. Prior work: the paper inclines on prior work, which posits that anomalies in stock market might stimulate ripples amongst market participants. Approach: BRICS countries’ stock market data for a period of 95 days between January and May 2020 were analysed for causality using the Vector Auto-regression and the Granger Causality Wald test. Findings: Stock performance in China and India during the COVID period can predict the stock performance in Brazil during the COVID period. In addition, stock performance in Russia and South Africa can predict stock performance in India during the COVID period. Implication: the findings provide additional investment information to clarify investment risks and uncertainty for current and potential investors in BRICS countries. This paper provides important academic case study for business schools and suggests future research agenda. Value: this article contributes the first empirical analysis of causal relationship amongst the BRICS market performance during the COVID-19 pandemic.